1998
DOI: 10.1159/000006834
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Wall Thickening Does Occur in Elite Power Athletes with or without Anabolic Steroid Use

Abstract: Reports on the occurrence of left ventricular wall thickening in resistance-trained athletes have rejected the possibility for this physiological adaptation to occur without concomitant anabolic steroid abuse. Others have concluded short bursts of arterial hypertension that occur with maximal weight lifting are not sufficient to induce left ventricular wall thickening, and left ventricular wall thickness ≥13 mm should not be found in pure resistance-trained athletes. Therefore, we examined 4 elite resistance-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 18 publications
1
23
2
4
Order By: Relevance
“…3 Fagard 16,17 observed that athletes engaged in static training had LV dimension increased 2.5% and LV wall thickness increased 12% compared with that in non-athletes. In addition, Dickerman et al 18 demonstrated that LV wall thickness >13 mm can be found routinely in elite resistance-trained athletes, and the use of anabolic steroids concomitant with resistance training does appear to augment LV mass. Normal or a slight increase in LV internal diameter and a large increase in LV wall thickness are commonly explained on the basis of the acute increase in blood pressure during resistance training.…”
Section: Cardiac Structure and LV Massmentioning
confidence: 99%
“…3 Fagard 16,17 observed that athletes engaged in static training had LV dimension increased 2.5% and LV wall thickness increased 12% compared with that in non-athletes. In addition, Dickerman et al 18 demonstrated that LV wall thickness >13 mm can be found routinely in elite resistance-trained athletes, and the use of anabolic steroids concomitant with resistance training does appear to augment LV mass. Normal or a slight increase in LV internal diameter and a large increase in LV wall thickness are commonly explained on the basis of the acute increase in blood pressure during resistance training.…”
Section: Cardiac Structure and LV Massmentioning
confidence: 99%
“…Alternatively, vocal cord paralysis could occur due to damage to the recurrent laryngeal nerves. Studies have demonstrated AAS to be neurotoxic when injected in the proximity of peripheral nerves [27]. Although the exact mechanism by which this occurs is poorly understood, it is postulated that AAS initiate the apoptotic cascade of neuronal cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…These changes may lead to hypertension, cardiac arrhythmias, congestive heart failure, heart attacks or sudden cardiac death [65]. Although these structural changes are also apparent in non-drug using athletes, use of AAS accelerate the process [66].…”
Section: Non Medical Use and Abuse Of Aasmentioning
confidence: 99%